Linguistic Attitudes towards British and American English in students of the English Specialty of San Marcos University - Cárdenas Cornelio, Yony (2022)
The objective of this research is to address the phenomenon of linguistic attitudes in students of the specialty of English. This will make it possible to distinguish the attitudes of learners regarding American English and British English in Spanish-speaking contexts. The study of linguistic attitudes is relevant in sociolinguistics because the wealth of information on the functioning of the language is in its social relationship with the community” (Holmes, 2013, pp. 1-2). Thus, this type of work comprises three areas: cognitive, behavioral and affective attitudes (Zanna and Rempet, 1988), which are considered in this study. The mask method survey and observation will be used as a means of investigation. The linguistic attitudes of the students of the English major at UNMSM regarding American and British English are positive due to the prestige that both languages ​​have and because of the integrative and instrumental attitudinal motivations. Regarding the sociolinguistic variables in relation to attitudes, it has only been possible to find a relationship of significant influence in age. In the analysis of the technique of the masks, a higher average of acceptance was evidenced in almost all the attributes with respect to British English.